Using the Collatz Conjecture, show how we get to "oneness" from 5632

We start with n = 5632

__Step 1 → n = 5632__

Since 5632 is even, we divide by 2 to get 5632 ÷ 2 = 2816

__Step 2 → n = 2816__

Since 2816 is even, we divide by 2 to get 2816 ÷ 2 = 1408

__Step 3 → n = 1408__

Since 1408 is even, we divide by 2 to get 1408 ÷ 2 = 704

__Step 4 → n = 704__

Since 704 is even, we divide by 2 to get 704 ÷ 2 = 352

__Step 5 → n = 352__

Since 352 is even, we divide by 2 to get 352 ÷ 2 = 176

__Step 6 → n = 176__

Since 176 is even, we divide by 2 to get 176 ÷ 2 = 88

__Step 7 → n = 88__

Since 88 is even, we divide by 2 to get 88 ÷ 2 = 44

__Step 8 → n = 44__

Since 44 is even, we divide by 2 to get 44 ÷ 2 = 22

__Step 9 → n = 22__

Since 22 is even, we divide by 2 to get 22 ÷ 2 = 11

__Step 10 → n = 11__

Since 11 is odd, we take 3(11) + 1 → 33 + 1 = 34

__Step 11 → n = 34__

Since 34 is even, we divide by 2 to get 34 ÷ 2 = 17

__Step 12 → n = 17__

Since 17 is odd, we take 3(17) + 1 → 51 + 1 = 52

__Step 13 → n = 52__

Since 52 is even, we divide by 2 to get 52 ÷ 2 = 26

__Step 14 → n = 26__

Since 26 is even, we divide by 2 to get 26 ÷ 2 = 13

__Step 15 → n = 13__

Since 13 is odd, we take 3(13) + 1 → 39 + 1 = 40

__Step 16 → n = 40__

Since 40 is even, we divide by 2 to get 40 ÷ 2 = 20

__Step 17 → n = 20__

Since 20 is even, we divide by 2 to get 20 ÷ 2 = 10

__Step 18 → n = 10__

Since 10 is even, we divide by 2 to get 10 ÷ 2 = 5

__Step 19 → n = 5__

Since 5 is odd, we take 3(5) + 1 → 15 + 1 = 16

__Step 20 → n = 16__

Since 16 is even, we divide by 2 to get 16 ÷ 2 = 8

__Step 21 → n = 8__

Since 8 is even, we divide by 2 to get 8 ÷ 2 = 4

__Step 22 → n = 4__

Since 4 is even, we divide by 2 to get 4 ÷ 2 = 2

__Step 23 → n = 2__

Since 2 is even, we divide by 2 to get 2 ÷ 2 = 1

## Collatz Conjecture Video